PENINGKATAN LITERASI MELALUI MENULIS PUISI DENGAN TEKNIK "STORYBOARDING" DIGITAL SISWA KELAS X SMA NEGERI 1 MEDAN - Shinta Uly M Sihombing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to improve students' literacy skills in writing poetry through the application of a digital storyboarding technique. The research employed a Classroom Action Research (CAR) method, which was conducted in two cycles involving 36 students of class X-2 at SMA Negeri 1 Medan in the 2024/2025 academic year. Each cycle consisted of planning, action, observation, and reflection stages. The digital storyboarding technique was utilized to assist students in visualizing ideas and emotions through images before expressing them in poetic form. The results revealed a significant improvement in students’ poetry writing abilities. In the initial stage, only a small number of students reached the Minimum Mastery Criterion (KKM) of 75. However, by the second cycle, all students (100%) achieved or exceeded the target score. In addition to academic improvement, students demonstrated higher levels of interest, creativity, and engagement during the learning process. The use of digital storyboarding effectively supported students’ imagination and helped them structure poetic lines meaningfully.